Towards a model to optimized collect of vital signs through adaptive strategies - Aranda, Jorge Arthur S.; Dias, Lucas P. S.; Wolf, Alexandre S.; Carvalho, Juliano V. de; Tavares, Maurício C.; Yamin, Adenauer C.; Barbosa, Jorge L. V. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2019)
Wearable devices have emerged from the advancement of communication technology and miniaturization of electronic components. These devices monitor periodically the user’s vital signs and generally have low battery autonomy. This article proposes ODIN, a model to optimized collect of vital signs based on adaptive strategies. The comparison with related works indicates that ODIN is the only proposal that presents an adaptive collect of vital signs, which enables the optimized generation of a historical contexts. A prototype was implemented and applied in an evaluation. The evaluation consists in a simulation with requests control in order to optimize the parameters of the collect allowed a 214% increase in battery life in adaptative scenario compared to a collect without adaptivity.